Macrofabric and grain size analysis of moraines and other till deposits in the Serra da Estrela Mountains, central Portugal - Santos, João Bessa (2020)
Till macrofabric and grain-size analysis of glacial diamictons and landforms present in several valleys of the Serra da Estrela Mountains in central Portugal were used to interpret till types and to reconstruct the glacial paleoprocess history of this mountainous region. Supraglacial melt-out and flow tills are dominant in this range. Supraglacial melt-out tills, representative of periods of glacial stability and stagnation followed by recession, present weaker fabric data and coarser, poorly sorted sediments. Flow tills, mainly representative of glacial stability followed by recession, present crude layering, and soft-sediment deformation structures with moderate fabric data and coarser to fine, poorly sorted sediments. Glacial diamictons affected by post-glacial paraglacial activity in the form of landslides were also observed in three valleys. These present weaker to moderate fabric data and coarser, poorly sorted sediments. These glacial diamictons and landforms are of particular importance in the reconstruction of the glacial dynamics and history of the Serra da Estrela Mountains due to a scarcity of chronological data based on absolute dating methods. These mountains also represent the southernmost Atlantic range in Europe where significant glaciation took place, which makes it an interesting area to investigate mountain glacial dynamics in low elevation humid Atlantic coastal ranges and compare it with other Atlantic ranges.